Modelling and Mechanical Characterization of a Metamaterial Inspired by the Spinodal Decomposition - Barbara Mandolesi; Christian Iandiorio; Valerio G. Belardi; Francesco Vivio (Engineering Proceedings, 2025)
The increasing interest in metamaterials stems from the ability to expand the design space for material properties by tailoring the material architecture. Spinodal decomposition-inspired topologies are an emerging class of minimal surface-based metamaterials with promising properties. The diffusion process of the binary mixture is modeled using the Cahn–Hilliard equation, which is typically approached with a statistical method (superimposition of Gaussian random fields) that is well founded only for its initial stages. In this work, a fast and efficient computational method based on the finite difference method is employed to simulate the entire 2D dynamic evolution. Next, the solution field is converted into a CAD model forming the metamaterial. The elastic properties are assessed using a computational homogenization in which both homogeneous displacement and periodic boundary conditions have been applied for comparison. Finally, results from experimental testing confirm the accuracy of the FE homogenization procedure developed here.